Perilaku Stress Kerja Dan Motivasi Kerja Pada Karyawan di Divisi SO (Signing Officer) Pada PT. Bank Tabungan Negara (Persero) Tbk Kc Medan - Azzahra Nasution, Annisaa Putri; Suhairi, Suhairi (LPPM Universitas Labuhanbatu, 2022)
In this research, the researcher chose SO Division employees (Signing Officer) as the subject which is one of the important divisions in completing the KPR contract at PT. State Savings Bank KC Medan. This study aims to analyze the level of work stress and work motivation obtained by employees of the SO (Signing Officer) division. The results of this study explain what things make employees' workloads causing work stress, and what things make employees motivated to work during the work process. The method used in this research is descriptive qualitative. The results of the analysis show that work stress occurs due to the burden of credit settlements from problematic customers and differences of opinion with the leadership which cause pressure on SO employees. Behind work stress, there is employee work motivation with the feedback they get.